2019
DOI: 10.3390/en12091675
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on the Energy Efficiency of a Parallel Hybrid Drive for an Inland Ship

Abstract: The growing requirements for limiting the negative impact of all modes of transport on the natural environment mean that clean technologies are becoming more and more important. The global trend of e-mobility also applies to sea and inland water transport. This article presents the results of experimental tests carried out on a life-size, parallel diesel-electric hybrid propulsion system. The efficiency of the propulsion system was analysed for two modes of operation (electric and diesel) and for different eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The second cluster solutions for reducing energy consumption and pollution concerns the strategies aimed at limiting the negative impact of all the modes of transport on the natural environment meaning that “clean” technologies are becoming increasingly important and widespread (Litwin et al 2019).…”
Section: Results From Camentioning
confidence: 99%
See 1 more Smart Citation
“…The second cluster solutions for reducing energy consumption and pollution concerns the strategies aimed at limiting the negative impact of all the modes of transport on the natural environment meaning that “clean” technologies are becoming increasingly important and widespread (Litwin et al 2019).…”
Section: Results From Camentioning
confidence: 99%
“…According to the literature, smart mobility plans to implement actions and reduce pollution and waste (Bueno-Delgado et al 2019; Litwin et al 2019; Yenneti et al 2019), while increasing transport efficiency (Li et al 2019). For this reason, smart mobility is deeply connected to the performance of sustainable mobility, contributing to improving the quality of life (Olaverri-Monreal 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While carrying out further work on electric and hybrid propulsion [19][20][21][22] on the occasion of a small inland shuttle ferry project for the city of Gdańsk (Figure 1), the designers paid particular attention to the problem of energy management [23][24][25][26]. It turned out that the classic methods of calculating the demand for propulsion power [27,28] are practically useless.…”
Section: The Problemmentioning
confidence: 99%
“…The motor is controlled by a frequency converter powered by a lithium battery set. During previous research, the energy efficiency of a similar propulsion system was measured and it was found that the energy efficiency of such a power unit exceeds 90% [20]. For further calculations, efficiency was assumed to be η mot = 0.9.…”
Section: Testsmentioning
confidence: 99%
“…The effect of radical hull shape changes can be analysed using computer simulations (strip or panel methods, CFD) [45]. The obtained research data can be used to increase the ship propulsion efficiency, and improve the safety and comfort of ship operation [26], [52], [53], [54], [55], [56]. However, bearing in mind enormous cost of shipbuilding, the predicted seakeeping characteristics obtained from numerical analyses for the ship to be built should be finally verified using experimental methods (in the towing tank, for instance).…”
Section: Introductionmentioning
confidence: 99%